Social media usage among wine tourism DMOs - Jorge, Filipa (2020)
Social media is an important tool for tourism destination promotion. The usage and the contents published on these platforms have an important role in visitors’ decision-making process. Information and communication technologies are changing DMOs’ markets and communication paradigm, since they allow the interaction between these organizations, visitors, and stakeholders. Therefore, social media are increasing their relevance on DMOs’ marketing strategies. This purpose of this study is to analyze comparatively social media platforms’ usage by six wine tourism DMOs. The results were provided by the analysis of secondary data available on these platforms and DMOs posts on the four most popular social media platforms to tourism industry: Facebook, Instagram, Twitter, and YouTube. Results indicate that DMOs use their official accounts on these platforms on different ways. This study also reveals that Facebook is more interactive than other platforms, and YouTube achieves less engagement levels.